Essentials of Marketing: A Global-managerial Approach (Mcgraw-Hill/Irwin Series in Marketing) - Mc Carthy E.Jerome (McGraw Hill/Irwin, 2006)
Essentials of Marketing is a brief version of Basic Marketing, the worldwide market leading Principles text. Basic Marketing and Essentials of Marketing are the first books to develop and present the 4Ps framework (Product, Price, Place, Promotion) which describes the components of the marketing mix and forms the foundation of Marketing. Like Basic Marketing, Essentials of Marketing offers a very thorough integration of the latest marketing themes, topics, and examples woven throughout.